THE CASTAGNONE SITE (CERRINA VALLEY, MONFERRATO HILLS, NW ITALY): EARLY PLEISTOCENE SEDIMENTARY RECORD AND BIOCHRONOLOGY (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2003)
Geological researches carried out near che Castagnone hamlet in che Cerrina Valley (Northem Monferrato Hills, Piedmont, NW Italy), have brought to light a post-Messinian succession whose sedimentary record starts with a Lower Complex of pedogenized colluvial materials and with two superimposed Alluvial Units (I and II). The lower one of these units contains a Galerian macrofauna associated with microtine vole teeth (Mimomys savini, Mimomys pusillus, Ungaromys cf. U. nanus, Microtus (Allophaiomys) sp.), while che upper one yields only scarce faunal remains. Most of this sediments were deposited during a normal palaeomagnetic phase. The I Alluvial Unit, due to its biochronological correlation, must be referred to the Jaramillo Subchron, between 1,070,000 and 990,000 years ago. The II Alluvial Unit, being both unconformable with and younger than the first one, might be best referable to the Brunhes Chron. Overall, the bed dipping across the reported succession shows a progressive syn-sedimentary tilting, with accelerated deformation during the I Alluvial Unit deposition. This tectonic stress over the Castagnone area is seemingly related to the uplift of the north-easternmost ridge of che Monferrato Hills and appears to have been nearly exhausted before the II Alluvial Unit deposition.